Dietary Changes During COVID-19 Lockdown in Adults With Type 1 Diabetes on a Hybrid Artificial Pancreas - Vetrani, Claudia; Calabrese, Ilaria; Di Rienzo, Silvia; Pagliuca, Mariasofia; Rivieccio, Annamaria; De Angelis, Raffaele; Riccardi, Gabriele; Rivellese, Angela Albarosa; Annuzzi, Giovanni; Bozzetto, Lutgarda (Frontiers in Public Health, 2021)
In this retrospective analysis, we examined the impact of lockdown for COVID-19 on eating habits in individuals with type 1 diabetes (T1D) on a hybrid artificial pancreas (HAP). Dietary composition before and during lockdown was assessed by 7-days food records in 12 participants with T1D on HAP (3 males/9 females, age 38±13 years, HbA1c 6.8±0.3%, M±SD). Continuous glucose monitoring (CGM) metrics and lifestyle changes (online questionnaire) were also assessed. Compared to pre-lockdown, reported body weight tended to increase during lockdown with no changes in total energy intake. Participants significantly decreased animal protein intake (-2.1±3.7% of total energy intake, p=0.048), whereas tended to increase carbohydrate intake (+17±28 g/day, p=0.052). These changes were induced by modifications of eating habits at breakfast and lunch during weekdays. Patients consumed more cereals (+21±33 g/day, p=0.038), whole grain (+22±32 g/day, p=0.044), and sweets (+13±17 g/day, p=0.021), and less animal protein sources (-42±67 g/day, p=0.054). Participants showed a more regular meal timing and a decreased physical activity. Blood glucose control remained optimal (Time-in-range 76±8% vs. 75±7% before lockdown) and daily total insulin infusion increased (42±10 vs. 39±12 I.U., p=0.045). During lockdown, T1D patients on HAP modified dietary habits decreasing animal protein and increasing carbohydrate intake. This increase, mainly concerning whole grain and low-glycemic-index products, did not influence blood glucose control.